BREACH OF PEACE AGREEMENT (HOMOLOGATION) BETWEEN PT LAUTAN WARNA SARI AND PT KERTAS LECES (PERSERO) - Maria Mahdalena Juniarti (Faculty of Law, Universitas Lampung, 2023)
Peace efforts filed by the business entity PT Kertas Leces (Persero) (hereinafter referred to as the Respondent) in the Debt Payment Obligation Postponement (PKPU) process in collaboration with PT Lautan Warna Sari (hereinafter referred to as the Applicant), which was ratified into a Peace Agreement (homologation) decided by the Commercial Court in Decision No. 05/PKPU/2014/PN.Niaga.Sby. The Peace Agreement (homologation) contains an agreement that must be fulfilled by the respondent to the applicant. However, in its implementation, the respondent was negligent and could not fulfill these provisions so that the applicant filed for cancellation of the peace agreement. The request was granted by the court through Decision Number 1/Pdt.Sus.Cancellation of Peace/2018/PN Niaga.Sby so as to declare the respondent bankrupt with all legal consequences. The research will discuss 2 (two) problems, namely (1) The legal consequences of breach on the peace agreement (homologation) between PT Lautan Warna Sari and PT Kertas Leces (Persero) and (2) Efforts to resolve breach on the peace agreement (homologation) between PT Lautan Warna Sari and PT Kertas Leces (Persero). The research uses a normative juridical approach, which is a study of the law that conceptualizes the law as norms, rules, regulations and applicable legislation. The research shows that the legal consequences of breach on the peace agreement (homologation) between PT Lautan Warna Sari and PT Kertas Leces (Persero) is the cancellation of the peace agreement because PT Kertas Leces as a debtor neglects to fulfill the agreement in the agreement so that the debtor is declared bankrupt. The debtor also bears compensation and risk transfer through the disposal of the debtor's bankruptcy assets by the curator. In addition, the debtor also pays court costs. Efforts to resolve breachs on the peace agreement (homologation) between PT Lautan Warna Sari and PT Kertas Leces (Persero) are through the administration of bankruptcy assets by concurrent with procedures, first, the debtor will pay preferred creditors, namely the normative rights of former employees. Second, the debtor will pay a percentage of the debtor's assets to the state treasury as non-tax revenue from bankruptcy. Third, the debtor will pay other creditors in accordance with their receivables.